Non‐Halogenated Solvents Processed Efficient ITO‐Free Flexible Organic Solar Cells with Upscaled Area. Issue 16 (31st March 2022) - Zhao, Feng; Zheng, Xiangjun; Li, Shuixing; Yan, Kangrong; Fu, Weifei; Zuo, Lijian; Chen, Hongzheng
Abstract: Organic solar cells (OSCs) show the potential to harness solar energy at a lower cost and in a greener way with the merits of mechanical flexibility and potential low‐cost upscaling production with solution processing. Meanwhile, the common use of toxic halogenated solvents causes pollution to the natural environment, and thus, needs to be avoided. Following the authors' previous work on the design of top‐illuminated ultrathin Ag‐based device structure highlighting most merits of OSC, herein non‐halogen solvent and additive processing OSCs are presented, which exhibit high power conversion efficiency (PCE) of 17.64%, close to the best PCE with the commonly used halogen solvent. Interestingly, it is observed that the additive and the multicomponent strategy (blending third component BTP‐S2 into PM6:L8‐BO binary blend) synergistically affect the optimal morphology and device performance. Finally, OSC devices featuring green solvent processing, indium tin oxide‐free, flexibility, and upscaling merits are fabricated and exhibit the best PCE of 13.76% with high mechanical robustness and good stability against heat or light illumination. This work provides a prospective potential for manufacturing the OSC toward practical applications. Abstract : Efficient organic solar cells, processed from non‐halogenated solvents and upscaled flexible fabrication, are demonstrated. By the use of toluene hydrocarbon solvent and 1‐PN non‐halogenated additive, 17.64% efficiency from PM6:L8‐BO:BTP‐S2 ternary devices is enabled, and the process of a 13.76% upscaled flexible indium tin oxide‐free device in top‐illumination structure is managed, which provides a good prospect for environmentally friendly process and industrialization.